Pengaruh Social Media Marketing dan E-Wom terhadap Keputusan Pembelian pada Glans Konveksi di Badung - Wiranata, I Putu Arya; Wimba, I Gusti Ayu; Mashyuni, Ida Ayu (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study aims to determine the influence of social media marketing and electronic word of mouth (e-wom) on purchasing decisions at Glans Convection in Badung. The population in this study was 1,149 people, where the determination of the number of samples used the slovin formula so that the number of samples was obtained as many as 92 respondents, which was then the method of determining samples using purposive sampling techniques. The data analysis technique used in this study is a test of research instruments which is then continued with multiple linear regression analysis, a coefficient of determination test,T test and F test. Social media marketing and electronic word of mouth (e-wom) simultaneously have a positive and significant effect on purchasing decisions. The advice given is so that Glans Convection in Badung maximizes the creation of interesting content and improves a fast, clear and informative response, especially if there are consumers who ask questions in the comments column.